Adoption of New Pedagogies for Curriculum Delivery in the Post Covid-19 (International Journal of Scientific Research and Management (IJSRM), 2024)
The purpose of this paper to advocate for embracing of new techniques of delivering lessons in institutions of higher learning. The advent of the global covid-19 pandemic has brought new challenges for the higher education space. The pandemic with its ‘new normal’ has challenged higher education institutions beyond just access to resources, however, with aspects of curriculum delivery. The ‘new normal’ has meant that curriculums need to be delivered online. Thus, many higher education institutions have had to involuntarily jump on the online teaching and learning bandwagon. The move to online teaching and learning for higher education institutions has resulted in several challenges as many higher education institutions have curriculums designed for traditional teaching (face-to-face) delivery. The challenges brought about by the Covid-19 pandemic and its “new normal” has shown that changes needs to happen to higher education curriculums to be able to overcome these challenges. Therefore, this paper recommends that post covid-19, face-to-face higher education institutions need to restructure their curriculums and adopt hybrid curriculums that incorporate online teaching and learning.